Modification of Natural Zeolite from Klaten, Indonesia Using Ammonium Chloride by Ion-Exchange and Its Application as Catalyst in Ethanol Dehydration to Produce Diethyl Ether - Zaira Adila; Wega Trisunaryanti; Triyono Triyono (Universitas Gadjah Mada, 2024)
Modification of a natural zeolite from Klaten, Indonesia, as a catalyst in the dehydration of ethanol to produce diethyl ether (DEE) has been conducted. Raw Klaten natural zeolite (ZA) was modified using 1 and 2 M of an ammonium chloride solution for 24 h while stirring for 18 h, then calcined at 500 °C for 5 h under N2 gas flow produced HZA1 and HZA2 catalyst, respectively. The catalysts were characterized using XRD, BET surface area, SEM-EDX, XRF, FTIR and gravimetric acidity test using ammonia-based vapor. The dehydration process was conducted under variations of temperature (200, 250, and 300 °C) and catalyst mass of 0.1, 0.2, and 0.4 g for 20 mL of 96% ethanol. The HZA1 catalyst produced the highest yield of DEE (2.41%) at 250 °C and 0.1 g catalyst. This catalyst showed needle-like of 66.22 nm crystal size, consisting of 32.57% mordenite, the highest surface area (48.32 m2/g), crystallinity (32.93%) and Brønsted acid sites (2.75 mmol/g), the lowest pore diameter (1.77 nm) and Si/Al mol ratio (4.03). The HZA1 catalyst can be used repetitively and produced DEE yield at the second and third runs (2.40 and 2.61%).